PEMBERIAN ABU SERBUK GERGAJI DAN PUPUK MAJEMUK NPK Mg PADA MEDIUM GAMBUT TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) FASE PEMBIBITAN UTAMA - Jamal, Rizkal Pasiri; Wardati, Wardati; Armaini, Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research effect in interaction sawdust ash and NPK Mg compound fertilizer on the growth of oil palm seedlings and to get the best combination for the growth of oil palm seedlings phase main nursery. This research was conducted in the experimental field and Laboratory of Production Faculty of Agriculture, University of Riau in Campus Binawidya Km 12.5 Simpang BaruPekanbaru. Have been implemented from Desember 2015 to Maret 2016.The research used Completely Randomized Design factorial that consisting of two factors. The first factor is sawdust ash(A) consists of four levels. The second factor is the NPK Mg fertilizer (N), which consists of 3 levels. Parametersmeasured were : seedling height increment,increase of leaves number, increase of hump diameter, root volume,seedling weight dry, ratio crown and root.Data obtained from the research results were statistically analyzed by analysis of variance followed by a further test of Duncan's New Multiple Range Test (DNMRT) at 5%. The results showed giving sawdust ash and NPK Mg compound fertilizer no interaction in all parameters the observation of oil palm seedling except ratio crown and root.Keywords : sawdust ash. NPK Mg compound fertilizer, the medium of peat, oil palm seedling.